Qualidade de produtos e serviços como diferencial competitivo para fidelização de clientes: - Marinho, Wendel Rocha (Universidade Federal do Tocantins, 2022)
n the scenario of difficulties encountered by car dealerships in loyalty is to provide their customers a quality service, this study aimed to investigate the importance of quality care and what can contribute to loyalty, and quality services provided to the customer at the concession, in the municipality of Araguaína-TO. The research was used only for descriptive statistical analyses with a questionnaire of self-prefilling carried out with 68 (sixty-eight) customers. Consequently customers are more discerning every day with a good impression in the quality service and above all, in the quality service, thus making a bridge to consumer satisfaction where the dealership in do the right service on the first visit.